CHARACTERISTICS OF DEVELOPING LEARNING MOTIVATION IN PRIMARY SCHOOL CHILDREN (World Bulletin of Education and Learning, 2025)
The purpose of this article is to examine and analyze the development of learning motivation and support in primary school students and to identify effective methods and conditions that facilitate its development.
Keywords: Development of learning motivation, support, primary school students, effective methods, conditions, development.